La audiencia única dentro del juicio laboral - Vélez Plua, Marco Antonio (2015)
This legal research work entitled: "The Unique Audience in the labor Judgment" whose overall objective is: To base a legal standard requiring celerity, effective judicial protection and safeguards the rights of the parties at the hearing by labor action. The central problem to which reference is made in this investigation is as follows; How will the delay of the hearings, preliminary and final in labor cases, violate the constitutional principles of speed and concentration ?. The specific objectives that make up this work are: a legal basis for the regulatory field hearings in labor lawsuits in Ecuador, analyze the procedure of first instance hearings labor trial and develop a proposal for reform of the Code of Labour, Articles 576, 577 and 581, where a single hearing is established in the first instance in the labor trial, to ensure the constitutional principle of celerity. . Finally, the proposal for the amendment of Article 576 of the Labour Code and the deletion of Article 577 and 581por the following is performed: Art. 576.- The Single Settlement Hearing, Evacuation Test and Resolución.- filing of an application in which the actor will announce the evidence and within a period of two days of receipt in court, the judge or the judge shall demand, order that cite the defendant handing him a copy of the complaint and given a period of twenty days to answer and announce the evidence attaching documentary evidence to disprove requested by the actor in his application, after which time the judge or judge, set date, day and time, so the only settlement hearing, evacuation and resolution testing is performed. In the only hearing the judge will verify that the subpoena has met the defendant; the judge will seek an agreement between the parties that will be approved by the judge in the act by ruling be final. The public hearing will be chaired by the trial judge in the presence of the parties and their defense attorneys and witnesses as may be to give their statements, questions the confessor or witnesses may not exceed thirty, must refer each question a single fact, be made orally and must be qualified by the judge at the time of its formulation, which may make additional questions or confessing declarant. Witnesses declared individually and may not witness or hear the statements of other persons who render their testimony and once rendered his statement, leave the courtroom. The parties may cross-examine witnesses. Receptadas statements at the hearing, the parties may claim in law. After the allegations made by the parties the judge or the judge announced orally at the hearing stating this resolution is to place without demand or properly supported and reasoned as prescribed by the Constitution and notify the judicial lockers and e-mail addresses that you have designated to receive notifications, that decision must be notified within ten days after the completion of the single hearing..